The Power Regulation System in Budi Darma's Short Story Presiden Jebule - Asri, Zietha Arlamanda; Istiningdias, Dini Sri (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2024)
The concept of power remains an eternal topic of discussion, as it permeates every aspect of human existence. Likewise, in literary works, the theme of power is a central topic for several writers. One of the Indonesian writers, Seno Gumira Ajidarma, argues that in literary works, the authors are free to write reality and voice criticism, hopes, and concerns of the people against the authorities. In his work “Presiden Jebule”, Aji Darma tries to show how power is regulated and imprisoning society through rules and punishment. The method used in this research is post-structuralism by Michel Foucault. The research finding focuses the story based on the relationship between power and punishment. The research results showed that in President Jebule's short story, there was a production of power where the people were afraid and obeyed all the rules created by Jebule. The regulations that require people to have hairstyles that match Jebule's have become the panoptic system that regulates them. The crucial idea is that anyone who does not comply with the rules made by Jebule will be subject to sanctions such as torture and capital punishment.